ChemInform Abstract: AlCl3‐Induced C—N Bond Formation Followed by Pd/C—Cu‐Mediated Coupling—Cyclization Strategy: Synthesis of Pyrrolo[2, 3‐b]quinoxalines as Anticancer Agents. Issue 8 (1st March 2013) - Prasad, Bagineni; Kumar, K. Shiva; Babu, P. Vijaya; Anusha, K.; Rambabu, D.; Kandale, Ajit; Vanaja, G. R.; Kalle, Arunasree M.; Pal, Manojit
Abstract The monosubstituted products (III) are readily converted to the target structures in the presence of terminal alkynes.